The Effect of Syllable-level Hyphenation on Novel Word Reading in Early Finnish Readers: Evidence from Eye Movements - Häikiö Tuomo; Luotojärvi Tinja (Routledge Journals. Taylor & Francis, 2022)
In early Finnish reading instruction, hyphens are used to denote syllable boundaries. However, this practice slows down reading already during the 1st grade. It has been hypothesized that hyphenation forces readers to rely more on phonology than orthography. Since hyphenation highlights the phonology of the word, it may facilitate reading during the very first encounters of the word. To assess whether this is the case, Finnish 1st and 2nd graders read stories about fictional animals while their eye movements were registered. Each story included four occurrences of a novel target (pseudo)word, hyphenated at the syllable level in half of the stories. Target words were read faster with repeated exposure but there were no effects regarding grade or hyphenation. The use of hyphenation does not give rise to enhanced processing of phonology in novel words and is likely to hinder the processes connected to the use of orthography.